2011
DOI: 10.3109/00365521.2011.603162
|View full text |Cite
|
Sign up to set email alerts
|

How are thiopurines used and monitored by Swedish gastroenterologists when treating patients with inflammatory bowel disease?

Abstract: Thiopurines are well established in the treatment of IBD among Swedish gastroenterologists. New and evolving knowledge about thiopurine therapy in IBD has been adapted to a large extent. Whether this change in clinical practice will have an impact on treatment outcomes has yet to be proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Despite the widespread use of thiopurines and the growing knowledge about their interindividual variations in metabolism, monitoring of thiopurine metabolites is not widely used: at least two recently published surveys reveal that determination of TPMT activity (genotype or phenotype), 6TGN or 6MMP levels is used by a relatively low proportion of IBD gastroenterologist, the availability or reimbursement issues being the most relevant obstacles 34 35…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…Despite the widespread use of thiopurines and the growing knowledge about their interindividual variations in metabolism, monitoring of thiopurine metabolites is not widely used: at least two recently published surveys reveal that determination of TPMT activity (genotype or phenotype), 6TGN or 6MMP levels is used by a relatively low proportion of IBD gastroenterologist, the availability or reimbursement issues being the most relevant obstacles 34 35…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…The results show that thiopurines are well established in the treatment of IBD and also new knowledge about thiopurine therapy largely has been adapted with a clear agreement regarding indications, dosing and monitoring, as reported by Hindorf and Andersson [12].…”
mentioning
confidence: 74%
“…Even though this study has important limitations such as the management of the patients including concomitant drugs, it is suggested that the practice of examining TPMT genotype and TPMT activity prior to starting therapy with thiopurines has improved our ability to manage these patients more effectively and safely than previously. The practice of monitoring thiopurine metabolism has been well established in several countries such as Sweden, UK, New Zealand [19,37,38], where the national guidelines for treatment of IBD state that TPMT genotype and/or phenotype determination should be considered in all patients prior to initiation of thiopurine treatment. Recently, Chouchana et al [18] proposed a therapeutic algorithm allowing a dosage individualization to optimize and secure the management of patients under thiopurines.…”
Section: Discussionmentioning
confidence: 99%